2012
DOI: 10.5402/2012/731072
|View full text |Cite
|
Sign up to set email alerts
|

Decentralization and School Management in Namibia: The Ideologies of Education Bureaucrats in Implementing Government Policies

Abstract: This paper defines ideology as the belief systems, attitudes, views, and mindsets of educationists which inform their work. It examines the ideologies of school inspectors, principals, and teachers in the implementation of decentralized, cluster-based educational change in Namibia (see Pomuti 2009). Data were collected in three diverse school clusters. Data analyses resulted in the ideologies of the educationists being characterised as authoritarian, bureaucratic, and managerial. The paper argues that while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…in Ongwediva, Rundu and Katima Mulilo, so-called coloured students were trained in their residential area of Khomasdal, outside the capital of Windhoek, and white student teachers had their training in Windhoek (Angula and Grant Lewis, 1997). Teacher training for the native population was based on the Christian National Education curriculum which excluded Mathematics and Science (Rowell, 1995) and had the overall aim of instilling the ideology and segregation practices of the apartheid regime (Pomuti and Weber, 2012). However, such rudimentary teacher training was an important source of employment for the native population, albeit with a low salary and generally poor working conditions.…”
Section: Namibia – Backgroundmentioning
confidence: 99%
“…in Ongwediva, Rundu and Katima Mulilo, so-called coloured students were trained in their residential area of Khomasdal, outside the capital of Windhoek, and white student teachers had their training in Windhoek (Angula and Grant Lewis, 1997). Teacher training for the native population was based on the Christian National Education curriculum which excluded Mathematics and Science (Rowell, 1995) and had the overall aim of instilling the ideology and segregation practices of the apartheid regime (Pomuti and Weber, 2012). However, such rudimentary teacher training was an important source of employment for the native population, albeit with a low salary and generally poor working conditions.…”
Section: Namibia – Backgroundmentioning
confidence: 99%
“…This chapter contributes to the literature assessing how government institutions affect human capital production by analyzing how decentralization in a low-income country. It, thus, adds to contributions such as Davies, Harber, and Dzimadzi (2003) who study decentralization in Malawi's education sector, while Pomuti and Weber (2012) investigate the role plays by decentralization policy in Namibia. There are some empirical pieces of evidence suggesting that decentralized supervision improves the professional development of teachers (see Esia-Donkoh and Ofosu-Dwamena (2014) for the study of Ghana, Pomuti and Weber (2012) in Namibia, and Tamukong (2004) presenting a decentralization model for Cameroon).…”
Section: Introductionmentioning
confidence: 99%
“…It, thus, adds to contributions such as Davies, Harber, and Dzimadzi (2003) who study decentralization in Malawi's education sector, while Pomuti and Weber (2012) investigate the role plays by decentralization policy in Namibia. There are some empirical pieces of evidence suggesting that decentralized supervision improves the professional development of teachers (see Esia-Donkoh and Ofosu-Dwamena (2014) for the study of Ghana, Pomuti and Weber (2012) in Namibia, and Tamukong (2004) presenting a decentralization model for Cameroon). But, some studies find that decentralization may have negative effects on funding allocation, with the largest portion of funding not reaching the target population (see Otieno and Nyangechi (2013) and Dembélé (2015)).…”
Section: Introductionmentioning
confidence: 99%
“…Pomuti and Weber (2012) further revealed that Namibian principals lack the leadership capacity to make focused decisions. As a result, they continue to use authoritarian leadership styles, resist interference in the daily management of their schools and are reluctant to assist or collaborate with other schools (Pomuti and Weber, 2012). On the other hand, researchers noted that there have been a few published studies on the development and leadership of language professional programmes and the evaluation of such programmes is not common (Coskun and Daloglu, 2010;Day, 1991;OECD, 2009;Samson and Collins, 2012;Weir and Roberts, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Namibian principals demonstrated inconsistency on how they understood their leadership roles (Hausiku, 2015), having ascended to leadership positions without orientation for principalship or formal certification, but mainly on the basis of having good classroom teachers and adequately carrying out their administrative duties (Government of the Republic of Namibia, 2007). Pomuti and Weber (2012) further revealed that Namibian principals lack the leadership capacity to make focused decisions. As a result, they continue to use authoritarian leadership styles, resist interference in the daily management of their schools and are reluctant to assist or collaborate with other schools (Pomuti and Weber, 2012).…”
Section: Introductionmentioning
confidence: 99%